2017
DOI: 10.1017/jlg.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of regional French accents in (northern) France, Belgium, and Switzerland

Abstract: This paper investigates whether European Francophone subjects are able to distinguish between regional French accents from (northern) France, Belgium, and Switzerland, and at what level of granularity. In total, samples from 120 speakers (from five different areas in each country under study) were presented to hundreds of native French listeners from these three countries. In a first set of experiments, listeners were asked to identify the speakers’ country of origin: they achieved 60% correct identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
1
5
0
2
Order By: Relevance
“…The experiment also provided more general insights into the process of dialect identification. At first sight, listeners appeared to better identify their own as opposed to the other dialect, as reported in several dialect recognition studies on other languages ( Williams et al, 1999 ; Gooskens, 2005 ; Boomershine, 2006 ; Baker et al, 2009 ; Yan, 2015 ; Avanzi and Boula de Mareüil, 2017 ). Our results and, in particular, the use of signal detection theory, offer an alternative interpretation.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The experiment also provided more general insights into the process of dialect identification. At first sight, listeners appeared to better identify their own as opposed to the other dialect, as reported in several dialect recognition studies on other languages ( Williams et al, 1999 ; Gooskens, 2005 ; Boomershine, 2006 ; Baker et al, 2009 ; Yan, 2015 ; Avanzi and Boula de Mareüil, 2017 ). Our results and, in particular, the use of signal detection theory, offer an alternative interpretation.…”
Section: Discussionsupporting
confidence: 59%
“…However, there is also some evidence for variation in the own-dialect response bias. Avanzi and Boula de Mareüil (2017) , who compared the effect of speaker and listener dialect on accent identification in French, found that the tendency to better identify one’s own as opposed to other dialects was more marked in Swiss than in Belgian and French participants. Although this interpretation remains speculative, it is possible that the federal, non-centralistic political organisation of Switzerland, together with the lack of an oral standard variety with high prestige, further enhances this own-dialect bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Une méthodologie à base de crowdsourcing (production participative à grande échelle) a depuis permis de passer à quelques centaines voire quelques milliers d'auditeurs, auxquels étaient présentés des accents français d'Amérique du Nord, d'Afrique et d'Europe (Boula de Mareüil et al, 2017), mais chaque variété était représentée par un seul locuteur. D'autres expériences ont été conduites, centrées sur la France, la Suisse et la Belgique, touchant également une large audience, à travers des sites grand public ou les réseaux sociaux (Avanzi & Boula de Mareüil, 2017). Au total, des échantillons (d'une durée comparable aux tests précédents, soit une douzaine de secondes), provenant de 120 locuteurs (de 5 régions différentes dans chacun de ces pays) ont été présentés à des centaines d'auditeurs de ces mêmes pays.…”
Section: Introductionunclassified